Identifying The dimensions of a Latent Thermal Storage Tank to Cover an Electrical Load during Peak Times (Damascus University Journal for engineering sciences, 2021)
The right choice of the dimensions of the heat storage tank as well as the phase change material are very important in determining the amount of stored thermal power and the speed of charging )discharging) that we could use later on in covering a certain on-peak electrical load. In this paper, we have determined the thermal tank dimensions to cover 10 tons of refrigeration (35 kW nominal capacity), and the maximum thickness of phase change material that we can obtain from a cylindrical surface analytically and numerically based on advanced simulation packages (ANSYS-Fluent). e have found the thickness on a cylindrical tube is 3.5 cm for a cooling temperature of  based on 8 hours of continuous work in charging mode. It has been found also that the thickness is not related to or a function to the diameter as well as the type of the pipe and it increases with lowering the temperature of the heat source.
Keywords: Latent Heat Thermal Storage System (LHTES); Latent Heat; Phase Change Material; Cylindrical Surface